Ethics-oriented Learning in Environmental Education Workplaces: An activity theory approach - Lausanne Olvitt (Environmental Association of Southern Africa, 2010)
In the context of increasing national and global environmental challenges and their implications for the working world, new ethics and practices are being introduced into workplaces that take better account of socio-ecological relations. Little is understood, however, about the nature of ethics-oriented workplace learning. Drawing on Cultural Historical Activity Theory (CHAT), which enables historically and contextually situated relational perspectives to emerge, this paper explores contradictions in the activity systems of two young environmental education learner-practitioners struggling to engage with the ethical dimensions of their professional work and the professional development course they are studying. The study focuses in particular on the environmental values and ethics component of their course - a year-long Learnership in Environmental Education, Training and Development Practices (EETDP). The paper reflects how tensions and contradictions within and between the interacting activity systems of the workplace, the course, and its regulating qualifications authority influence the teaching and learning of the environmental ethics component of the course. Ethics-oriented teaching and learning processes are found to be strongly influenced by the 'rules' and 'mediating tools' of these interacting systems, but these are often at odds with the ethical perspectives, socio-cultural context and skills of the 'subject' and 'community'. These systemic contradictions can be more fully understood when their cultural and historical origins are made explicit. The analytical process has led to a more nuanced understanding of ethics-oriented teaching and learning in a workplace-based course, and has revealed several areas needing more careful research (particularly the area of environmental discourses) and the explicit and implicit language of ethics.